The Effect Of Product Type And Price On Consumer Purchase Decisions At Pt. Benelli Anugerah Heritage Motorcycle In Medan - Sitompul, Melisa Septiani; Asnawi, Muhammad; Firah, Al (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Every company has an interest in providing information to consumers and offering a variety of product types and the best prices.Price is also one wayto increase the number of customers. The purpose of this study is to determine the effect of product type on consumer purchasing decisions at PT. Benelli Anugerah Motor Pusaka in Medan. To determine the effect of price on consumer purchasing decisions at PT. Benelli Anugerah Motor Pusaka in Medan. To determine the effect of product type and price on consumer purchasing decisions at PT. Benelli Anugerah Motor Pusaka in Medan. The data analysis techniques used are validity test, normality test and multiple linear regression. The sample studied was 92 respondents. The results of this study obtained the significance value of product type on purchasing decisions based on the t test obtained tcount> ttable (2.024> 1.661961) H0 is rejected and Ha is accepted. The conclusion: there is a significant influence of product type on purchasing decisions. From the results of this study, the significance value of price based on the t test obtained tcount> ttable (6.778> 1.661961). The conclusion: then H0 is rejected and Ha is accepted, there is a significant influence of price on purchasing decisions. Based on the results of the F test above, the Fcount value> Ftable of (146.319>2.36) was obtained, which means that the product type and price variables simultaneously have a real (significant) influence or have a positive influence on the purchasing decision variable.